Differences in Carotid Plaques Between Symptomatic Patients With and Without Diabetes Mellitus: A CARE-II Study. Issue 6 (June 2019) - Gao, Xiao; Song, Jinyu; Watase, Hiroko; Hippe, Daniel S.; Zhao, Xihai; Canton, Gador; Tian, Fengshi; Du, Ran; Ji, Shengzhang; Yuan, Chun
Abstract : Objective—: Diabetes mellitus is associated with high-risk atherosclerotic plaques. This study aimed to compare characteristics of carotid atherosclerotic plaques in symptomatic Chinese diabetic and nondiabetic patients using vessel wall magnetic resonance imaging. Approach and Results—: Patients with cerebral ischemic symptoms in the anterior circulation and carotid atherosclerotic plaque determined by ultrasound were recruited from a cross-sectional, observational, multicenter study of CARE-II (Chinese Atherosclerosis Risk Evaluation). All patients underwent magnetic resonance imaging for carotid arteries. The morphological and compositional characteristics of carotid plaques were compared between diabetic and nondiabetic patients using linear (continuous variables) and logistic regression (binary variables). In a total of 584 recruited patients, 182 (31.2%) had diabetes mellitus. From the univariate analysis, diabetic patients had significantly greater mean wall area (33.7 versus 31.1 mm 2 ; P =0.002), maximum wall thickness (3.2 versus 2.8 mm; P <0.001), and mean normalized wall index (43.8% versus 41.0%; P <0.001) and had significantly higher prevalence of calcification (51.6% versus 36.6%; P =0.001), lipid-rich necrotic core (77.5% versus 58.5%; P <0.001), and high-risk plaque (29.7% versus 19.9%; P =0.011) than nondiabetic patients. After adjusting for clinical characteristics, the differences in presence of calcification ( P =0.018) and lipid-rich necrotic core ( P =0.001) remained statistically significant. Conclusions—: Symptomatic Chinese diabetic patients are more likely to have carotid plaques with calcification and lipid-rich necrotic core than nondiabetic patients, suggesting that diabetic patients may develop more severe atherosclerotic disease that should be accounted for in their clinical management. Abstract : Supplemental Digital Content is available in the text.